Espace, territoire, lieu, au crible de la géographie politique. L’émergence de l’Etat à Djibouti - Christian Bouquet (L'Espace Politique)
It is a question of revisiting some of the concepts on which juggles the classic geography for two or three decades, as space, territory, place, or still stream, network, and maybe also border, country, region – and State – by choosing illustrations in the Horn of Africa. This text thus tries to give a new lighting to the political geography.